Vaccinium vitis-idaea L.: Chemical Contents, Pharmacological Activities - Arnold Alexeevich Shamilov; Valentina Nikolaevna Bubenchikova; Maxim Valentinovich Chernikov; Dmitryi Igorevich Pozdnyakov; Ekaterina Robertovna Garsiya (Tabriz University of Medical Sciences, 2020)
One of the most known species of the genus Vaccinium (Ericaceae) is Vaccinium vitis-idaea L. or lingonberry. Leaves are included in the State Pharmacopoeia of the Russian Federation (XIV-th edition) and the State Pharmacopoeia of the Republic of Belarus (II-nd edition). The aim of this review is an analysis of data about a chemical content and types of pharmacological activities of Vaccinium vitis-idaea L. to discuss the tendency of future investigations on this plant. The main parts of works describe researches of chemical contents of fruits as medicinal and edible plant material. The majority of researches describe results of in vitro experiments. A significant interest is the study of the neuroprotective activity of the Vaccinium vitis-idaea extracts as well as their anti-cytokine and antiapoptotic properties and metabolic effects. The main biologically active compounds are phenologlycosides, tannins, proanthocyanes, saponins etc. These results will be of great significance for the development of new drugs from this plant and use along with the fruits of other parts of the plant.